Williams Obstetrics - Hauth, John C.; Bloom, Steven L.; Cunningham, F. Garay; Leveno, Kenneth J. (New York : McGraw Hill, 2005)
Overview: Obstetrics in broad perspective. Anatomy and physiology: Maternal anatomy. Implantation, embryogenesis, and placental development. Foetal Growth and development. Maternal physiology. Parturition. Antepartum. Preconception counselling. Prenatal care. Abortion. Ectopic pregnancy. Gestational trophoblastic disease. Genetics. Prenatal diagnosis and foetal therapy. Teratology, drugs and other medications. Antepartum assessment. Ultrasonography and doppler. Labour and delivery. Normal labour and delivery. Intrapartum assessment. Obstetrical anaesthesia. Dystocia-Abnormal labour. Disorders of amniotic fluid volume. Induction of labour. Forceps delivery and vacuum extraction. Breech presentation and peripartum hysterectomy. Prior caesarean delivery. Abnormalities of the placenta, umbilical cord and membranes. Foetus and newborn: The newborn infant. Diseases and injuries of the foetus and newborn. The puerperium. Puerperal infection. Obstetrical complications: Hypertensive disorders in pregnancy. Obstetrical haemorrhage. Preterm birth. Foetal growth disorders. Medical and surgical complications: General considerations and maternal evaluation. Critical care and trauma. Obesity. Cardiovascular disease. Chronic hypertension. Pulmonary disorders. Thromboembolic disorders. Renal and urinary tract disorders. Haematological disorders. Diabetes. Dermatological disorders. Neoplastic diseases. Infections. Sexually transmitted disease.
Keywords: CAVIDAD UTERINA; PLACENTA; PRENATAL; SISTEMA CARDIOVASCULAR